Synthesis, characterization and reactivity of a series of alkaline earth and rare earth iminophosphoranomethanide complexes - Matthew P. Stevens; Yu Liu; Elias Alexopoulos; Shifaa S. A. Xec Daudo; Rebecca R. Hawker; Adam Khan; Luis Lezama; Daniel Reta; Fabrizio Ortu (Communications Chemistry)
Abstract There is a great demand from the synthetic community for readily accessible organometallic alkaline earth and rare earth compounds that can be used as synthons for the preparation of new complexes and materials. Here we report the use of the methanide ligand {CH(SiMe3)P(Ph)2 = NSiMe3}– (NPC-H) in the stabilization of alkaline earth and rare earth organometallics and their potential use as synthetic precursors. Bis- and tris-methanide complexes were obtained following two methods: (1) deprotonation of the proligand with organometallic precursors; (2) salt elimination reactivity between potassium methanide and metal iodides. All compounds were characterised by multinuclear nuclear magnetic resonance, infra-red spectroscopy, elemental analysis, ultraviolet-visible spectroscopy and single crystal X-ray diffraction. Additionally, selected rare earth methanides were tested as synthetic precursors for the preparation of solvent-free rare earth complexes. Finally, the electronic structures of open-shell divalent rare earth methanides were probed using electron paramagnetic resonance, magnetometry studies and ab initio calculations.